Comparison of conventional CTA and volume perfusion CTA in evaluation of cerebral arterial vasculature in acute stroke - Saake, Marc; Gölitz, Philipp; Struffert, Tobias; Breuer, Lorenz; Volbers, Bastian; Dörfler, Arnd; Kloska, Stephan (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: CTA-like datasets can be reconstructed from whole-brain VPCTA. The aim of our study was to compare VPCTA with CTA for detection of intracranial stenosis and occlusion in stroke patients. Omitting CTA from stroke CT could reduce radiation dose. MATERIALS AND METHODS: One hundred sixty-three patients were included in this retrospective analysis. Inclusion criterion was suspected stroke within 4.5 hours after onset of symptoms. All examinations were performed on a 128-section multidetector CT scanner. Axial, coronal, and sagittal maximum intensity projections were reconstructed from CTA and from peak arterial phase of VPCTA. Images were scored for quality and presence of intracranial stenosis >50% or occlusion. For statistical analysis, the Wilcoxon signed-rank test and Fisher exact test were used, with a 2-tailed P value of .05 or less for statistical significance. RESULTS: Average image quality was superior in CTA (P < .05). However, image quality dichotomized for diagnostic significance was without difference between CTA and VPCTA (P > .05). Comparative statistical analysis revealed no significant difference for detection of intracranial stenosis and occlusion between CTA and VPCTA (P > .05). Substitution of intracranial CTA by VPCTA would lower radiation dose by 0.5 mSv. CONCLUSIONS: VPCTA is suited to assess the intracranial vasculature in patients with stroke and might have the potential to decrease radiation dose by substituting for intracranial CTA in stroke CT. Additional studies are necessary to further evaluate potential benefits of the dynamic nature of VPCTA.
CRIS-Team Scopus Importer:2022-08-05